Immunodetection of Leishmania Infantum in the Subungual Area of Dogs with Visceral Leishmaniasis - Henrique Leal Bertolo, Paulo; Eduarda Bastos Andrade Moutinho da Conceição, Maria; Rodrigues Reina Moreira, Pamela; Campos de Souza, Damazio; Bernadete Rozza, Daniela; Silva Cipriano, Rafael; Amoroso, Lizandra; de Oliveira Vasconcelos, Rosemeri (Journal of Veterinary Healthcare, 2019)
Onychogryphosis is one of the main clinical findings in dogs with visceral leishmaniasis (VL); however, research focusing on the subungual area of infected dogs is scarce. This study aims to assess the subungual area of dogs with VL that presented or not onychogryphosis by means of histopathological analyses and immunohistochemical studies (parasite burden). The third digit of the thoracic and pelvic limbs of Leishmania infantum naturally infected dogs was collected regardless of sex, breed or age. The animals were split into two groups, dogs with onychogryphosis (G1; n=7) and without onychogryphosis (G2; n=9). The digits were evaluated in four areas (dorsal epidermis/dermis, ventral epidermis/dermis, dorsal matrix/dermis and ventral matrix/dermis). All lesions observed (mononuclear inflammatory infiltrate, vacuolar degeneration of basal keratinocytes, dermoepidermal clefting and pigmentary incontinence) were present in both groups, being more severe in the digits of G1 group. Immunostaining of the amastigote forms of Leishmania infantum were observed in the different areas of the digit, with statistical difference between the dorsal epidermis/dermis area and the dorsal matrix/dermis of G1 group. In conclusion, the main histopathological alteration of the digit of dogs with VL is mononuclear inflammatory infiltrate and parasite burden, especially in cutaneous tissue adjacent to the nail matrix. This aspect can influence the onychogryphosis development, due to the presence of the parasite and by inflammatory mediators released in the nail microenvironment.
Keywords: dog; visceral leishmaniasis; digit; onychogryphosis